Complexity of glandular architecture should be reconsidered in the classification and management of endometrial hyperplasia. Issue 6 (19th March 2019) - Travaglino, Antonio; Raffone, Antonio; Saccone, Gabriele; Mollo, Antonio; De Placido, Giuseppe; Mascolo, Massimo; Insabato, Luigi; Zullo, Fulvio
Abstract : The 2014 World Health Organization (WHO) classification of endometrial hyperplasia (EH) defines premalignant EH based on only cytologic atypia, disregarding architecture complexity. We aimed to assess the impact of architecture complexity on the risk of cancer in non‐atypical EH. A systematic review and meta‐analysis was performed by searching electronic databases form their inception to October 2018. All studies assessing the rates of progression to cancer in non‐atypical EH (simple vs complex) were included. Pooled relative risk (RR) for cancer progression was calculated; a p‐value < 0.05 was considered significant. Eight studies with 1066 women were included. The risk for progression of non‐atypical EH to cancer was significantly higher in complex EH than in simple EH (p < 0.0001), with an RR of 4.90. In conclusion, the complexity of glandular architecture significantly increases the risk of cancer in non‐atypical EH. Complex non‐atypical EH may be regarded as a low‐risk premalignant lesion rather than a benign condition.